The Pivotal Role of Cooperative Learning Activities in Indonesian EFL Learning Contexts - Kristian Florensio Wijaya (ELT Worldwide: Journal of English Language Teaching, 2022)
To fulfill our nation’s mission in breeding more proficient, autonomous, and compassionate future professionals, educationalists are commissioned to divert their old teacher-centered teaching belief into a more student-centered approach. One of the integrative 21st-century teaching approaches worthwhile to be cultivated in our ELT enterprises is cooperative learning. Previous researchers overtly theorized that cooperative learning activities promoted a higher degree of second language enjoyable learning experiences transfiguring learners to be more highly responsible, competent, socialized, and compassionate academicians. This current qualitative library study aimed to delve more profoundly into the pivotal role of cooperative learning activities in Indonesian EFL learning contexts to encourage all ELT parties to apply this relevant student-centered learning approach in their variegated classrooms. To fulfill this research objectivity, some relevant major findings yielded by 30 cooperative learning studies were critically integrated to produce more robust research results. Based on the data analysis, it was found out that Indonesian EFL learners have gradually transformed into more professional future academicians upholding life-long learning behavior. Hence, it can be phrased that cooperative learning activities are one of the supportive learning methods rewarding to be internalized in daily-based Indonesian EFL classroom vicinities.Keywords: cooperative learning activities, EFL learning contexts, qualitative library study